Restoration of Central Power or Betrayal of Regional Autonomy? Analysis of the Impact of Recentralization of Mining Authority in the Era of Limited Autonomy - Rijal, Syamsul; Ilmar, Aminuddin; Maskun, Maskun; Ab Rahman, Nurul Hidayat (Journal of Law and Legal Reform, 2024)
This study analyzes the impact of re-centralizing mining authority on regional autonomy in Indonesia, focusing on legislative changes from Law No. 22/1999 to the Omnibus Law (Law No. 6/2023). The shift from decentralized to centralized control, accelerated by Law No. 3/2020, transfers authority from districts to provinces, aiming to improve national resource management efficiency. However, the findings reveal critical risks, including weakened environmental oversight, restricted public participation, and reduced local revenues from mining operations. While centralization may streamline governance, it poses significant challenges for regional governments in managing resources independently, impacting local welfare and sustainable development. This research offers novel insights into the tension between national efficiency and regional autonomy, emphasizing the urgency of re-evaluating policies to balance these interests. The study contributes to the broader discourse on governance by providing policy recommendations for achieving sustainable resource management within a decentralized framework.